Case study of the effects of organic soil amendments in reducing iron and aluminium in ex - mining bauxite area in growing media / Azizi Abd Wahab - Abd Wahab, Azizi (Faculty of Plantation and Agrotechnology, 2017)
Bauxite is a mineral that can be found below the sub soil. Mining is a method to obtain the bauxite but mining can cause changing topography, soil fertility and also soil structure. A study was conducted in rain shelter at Universiti Teknologi Mara (UiTM) Jasin Campus, Melaka for 3 months to investigate the effect of organic soil amendments on ex mining soil in reducing the iron and aluminium element, increase other macro elements and evaluate the growth performance of oil palm seedlings growing in ex mining bauxite land as planting medium. The soil was collected from ex-mining bauxite areas located at Kuantan, Pahang. The oil palm variety used was GH 500 that come from cross pollination between Elite Deli Dura and second generation of Psifera (BM 119). This research was arranged in randomized complete block design (RCBD) with five treatments. The treatments were (0) 100% soil, (1) soil and empty fruit bunches (EFB), (2) soil and goat manure, (3) soil and chicken manure, (4) soil and cow manure. The seedlings were supplied with water by using fertigation system for 10 minutes, twice per day. The data was collected once a month for 3 months. The results showed that the medium of (1) empty fruit bunch (EFB) was the best medium as it indicated highest results for most parameters observed in the study. Medium containing ex-mining bauxite soil mixed with empty fruit bunch showed the ability to reduce iron and aluminium element, increase other macro element and better seedling growth performance as indicated by the greater number of leaf and plant height.